2022
DOI: 10.1002/rmv.2381
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the SARS‐CoV‐2 omicron variants BA.1 to BA.5: Implications for immune escape and transmission

Abstract: The first dominant SARS‐CoV‐2 Omicron variant BA.1 harbours 35 mutations in its Spike protein from the original SARS‐CoV‐2 variant that emerged late 2019. Soon after its discovery, BA.1 rapidly emerged to become the dominant variant worldwide and has since evolved into several variants. Omicron is of major public health concern owing to its high infectivity and antibody evasion. This review article examines the theories that have been proposed on the evolution of Omicron including zoonotic spillage, infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
278
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(345 citation statements)
references
References 163 publications
10
278
0
2
Order By: Relevance
“…Plasma from convalescent human cases and from individuals who had been vaccinated against SARS-CoV-2 exhibited marked reductions in neutralizing activity against Omicron than against the ancestral SARS-CoV-2 (22)(23)(24)(25)(26). Multiple lineages of the Omicron variants have emerged including BA.1, BA.2, BA.3, BA.4 and BA.5, with the dominant strain being replaced by an emerging variant (27). Initially, BA.1 was the most prolific sublineage detected worldwide; however, BA.2 is overtaking BA.1 as the dominant variant and now BA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma from convalescent human cases and from individuals who had been vaccinated against SARS-CoV-2 exhibited marked reductions in neutralizing activity against Omicron than against the ancestral SARS-CoV-2 (22)(23)(24)(25)(26). Multiple lineages of the Omicron variants have emerged including BA.1, BA.2, BA.3, BA.4 and BA.5, with the dominant strain being replaced by an emerging variant (27). Initially, BA.1 was the most prolific sublineage detected worldwide; however, BA.2 is overtaking BA.1 as the dominant variant and now BA.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, BA.1 was the most prolific sublineage detected worldwide; however, BA.2 is overtaking BA.1 as the dominant variant and now BA. 5 has replaced (27). In human cases, lower neutralizing antibody titers against the BA.4 and BA.5 subvariants than against the BA.1 and BA.2 subvariants suggest that the Omicron variant is continuing to evolve with increasing capacity for neutralization escape (28).…”
Section: Discussionmentioning
confidence: 99%
“…BA.2 exhibits a 1.3- to 1.5-fold higher transmissibility and a 1.3-fold immune escape than BA.1 (16, 19), consistent with the finding that BA.1-immune sera neutralizes BA.2 with lower titers by a factor of 1.3 to 1.4 (20) and that BA.2 reinfection can occur after BA.1 (21). BA.4/BA.5 are more transmissible and resistant to BA.1/BA.2-immunity and monoclonal antibodies (1, 2). While BA.2 vs. BA.1 (19) and BA.4/BA.5 vs. BA.2 (22) display greater cell-to-cell fusion, they do not make infected people sicker nor change the fundamental pandemic dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 Omicron lineage has swept the globe with a rapid succession of dominating subvariants from BA.1, BA.2 and to the current BA.5 that takes up more than 90% infection cases with overriding edges in transmissibility and neutralizing antibody escape (1)(2)(3)(4)(5)(6)(7). Relative to Delta variant, Omicron BA.1 does not require fusion co-receptor TMPRSS2 for cell entry; instead, cells engulf it and land intracellularly through endosomes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…One article review [2] concluded that the Omicron variant causes mild, clinical symptoms but is more infectious than earlier variants. The spread of Omicron was important implications, might require urgent public health interventions to limit transmission, and reduced morbidity [3], especially in crowded region. Approximately 86.6% of the population in Macao completed at least two doses of COVID-19 vaccination [4], but immune escape of the Omicron variant resulted in reduced efficacy of existing vaccines and an increased risk of reinfection [5] coupled with treatment and detection failures [6].…”
Section: Introductionmentioning
confidence: 99%